Resolution of inflammation following treatment of ankylosing spondylitis is associated with new bone formation - Susanne J. Pedersen (2018)
Objective. To test the hypothesis that in patients with ankylosing spondylitis (AS) a vertebral corner inflammatory lesion (CIL) visible on magnetic resonance imaging (MRI) that completely resolves following treatment with anti-tumor necrosis factor-α (TNF-α) agents is more likely to develop into a de novo syndesmophyte visible on a radiograph as compared to a vertebral corner with no CIL. Methods. Fifty patients with AS, who had MRI at baseline and at followup (mean 19.2 months), and spinal radiography at baseline and after 2 years, were followed prospectively. A persistent CIL was defined as being present on both MRI, while a resolved CIL was defined as present at baseline MRI and completely disappeared at followup MRI. Two readers read the MRI independently, and analyses were done for areas with agreement (concordant reads) and for individual reads. Results. For patients receiving anti-TNF therapy (n = 23), new syndesmophytes developed more frequently from vertebral corners where a CIL had completely resolved on followup MRI (42.9% on concordant reads) as compared to vertebral corners where no CIL was demonstrable on either the baseline or followup MRI (2.4%; p < 0.0001). Results from individual readers showed similar differences. For patients receiving standard treatment (n = 27), the same pattern, although nonsignificant, was observed (20% vs 3.3%; p = 0.16) on concordant reads, as well as on individual reads. Conclusion. Our study of AS spines documents that MRI findings predict new bone formation on radiograph. Demonstration of an increased likelihood of developing new bone following resolution of inflammation after anti-TNF therapy supports the theory that TNF-α acts as a brake on new bone formation. Because the number of new syndesmophytes was low, further study is necessary to make firm conclusions. The Journal of Rheumatology Copyright © 2011. All rights reserved.